Potensi Tumbuhan Poguntano Sebagai Antidiabetes - Julia Susanti; Cut Masyithah Thaib; Hana Ike Dameria Br Purba (Universitas Sari Mutiara Indonesia, 2022)
Background: Diabetes is a dangerous degenerative disease. It even includes adiseasethatis classified as high risk because it can end in death. Diabetes is a heterogeneous syndrome whose overall symptoms are characterized by increased blood sugar levels caused by relative or absolute insulin deficiency. Based on research by Harahap, et al., 2013 and Febby, 2017 Poguntano has chemical compounds that have the potential as antidiabetic compounds, namely saponins as evidenced by the results of research with phytochemical screening results. This study aimstoexa mine the potential of the Poguntano plant as an antidiabetic. This research was conducted using the narrative review method, namely reviewing research articles, research journals, and these relating to the research subject, namely the Poguntano plant has the potential as an antidiabetic in the last 10 years, namely 2011-2021 through a search engine on Google Scholar database, PubMed, and Science Direct with the keywords “antidiabetic, Picria fel-terrae Lour.”. Then proceed with reviewing the articles so that a narrative review will be produced. Based on the results of the collection and selection of articles that have been carried out as the main references reviewed in this study, 11 references were obtained that met the inclusion criteria, research objectives, and journal quality. The results of research conducted by several researchers show that the poguntano plant has potential as an anti-diabetic and even the potency of poguntano is comparable to metformin which is generally used in the treatment of diabetes. Poguntano plant has antidiabetics properties. Where previous studies have conducted tests on animals as well as tests on humans and the results obtained that the poguntano plant is capable and very good at reducing diabetes levels.